Genome-Wide Identification of the Early Flowering 4 (ELF4) Gene Family in Cotton and Silent GhELF4-1 and GhEFL3-6 Decreased Cotton Stress Resistance - Tian, Miaomiao; Wu, Aimin; Zhang, Meng; Zhang, Jingjing; Wei, Hengling; Yang, Xu; Ma, Liang; Lu, Jianhua; Fu, Xiaokang; Wang, Hantao; Yu, Shuxun (Frontiers in Genetics, 2021)
The early flowering 4 (ELF4) family members play multiple roles in the physiological development of plants. ELF4s participated in the plant biological clock’s regulation process, photoperiod, hypocotyl elongation, and flowering time. However, the function in the ELF4s gene is barely known. In this study, 11, 12, 21, and 22 ELF4 genes were identified from the genomes of Gossypium arboreum, Gossypium raimondii, Gossypium hirsutum, and Gossypium barbadense, respectively. There ELF4s genes were classified into four subfamilies, and members from the same subfamily show relatively conservative gene structures. The results of gene chromosome location and gene duplication revealed that segmental duplication promotes gene expansion, and the Ka/Ks indicated that the ELF4 gene family has undergone purification selection during long-term evolution. Spatio-temporal expression patterns and qRT-PCR showed that GhELF4 genes were mainly related to flower, leaf, and fiber development. Cis-acting elements analysis and qRT-PCR showed that GhELF4 genes might be involved in the regulation of abscisic acid (ABA) or light pathways. Silencing of GhELF4-1 and GhEFL3-6 significantly affected the height of cotton seedlings and reduced the resistance of cotton. The identification and functional analysis of ELF4 genes in upland cotton provide more candidate genes for genetic modification.